Survey on trust evaluation mechanism in sensor-cloud - Tian WANG; Guangxue ZHANG; Shaobin CAI; Weijia JIA; Guojun WANG (Tongxin xuebao)
Sensor-cloud has gradually developed into a research hotspot.A good trust evaluation mechanism can better address some security issues in this new structure,such as internal attacks.A good trust evaluation mechanism can also ensure the security and efficient transmission of information in this structure.After an extensive research on sensor-cloud and trust evaluation mechanisms,it was found that trust evaluation mechanisms in sensor-cloud can be divided into two categories,among entities and in entity.After comparing the advantages and shortcomings of existing trust evaluation mechanisms,a new fog-based trust evaluation mechanism was designed and future research directions of trust evaluation mechanisms were discussed in sensor-cloud.